2020
DOI: 10.1186/s40662-020-00205-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes with a new design in multifocal intraocular lens: a pilot study

Abstract: Purpose: To evaluate the clinical and visual outcomes, quality of near vision and the influence of photic phenomena in patients bilaterally implanted with a new Precizon Presbyopic multifocal intraocular lens (IOL). Methods: In this prospective consecutive case series, 20 eyes of 10 patients were included (mean age 63.80 ± 12.55 years). Uncorrected and corrected visual acuity (far, intermediate and near), subjective refraction, binocular defocus curve, contrast sensitivity (CSV-1000) and quality of vision and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
7
8
2
Order By: Relevance
“…In our prospective study, 50% of patients reported being satis ed or very satis ed with the visual result, being able to perform between 70 and 80% of the intermediate vision tasks without glasses and between 40 and 70% of the near vision tasks vision without glasses. The results of our study are inferior to those of other publications of EDOF IOLs implanted in patients without ophthalmological comorbidities [42][43][44], and are more in line with the outcomes from Baartman et al [41]. In our retrospective study, 60% of patients reported being satis ed or very satis ed with the visual result and could comfortably perform between 60 and 80% of near vision activities without glasses.…”
Section: Discussioncontrasting
confidence: 75%
“…In our prospective study, 50% of patients reported being satis ed or very satis ed with the visual result, being able to perform between 70 and 80% of the intermediate vision tasks without glasses and between 40 and 70% of the near vision tasks vision without glasses. The results of our study are inferior to those of other publications of EDOF IOLs implanted in patients without ophthalmological comorbidities [42][43][44], and are more in line with the outcomes from Baartman et al [41]. In our retrospective study, 60% of patients reported being satis ed or very satis ed with the visual result and could comfortably perform between 60 and 80% of near vision activities without glasses.…”
Section: Discussioncontrasting
confidence: 75%
“…Multifocal IOLs have demonstrated good postoperative vision at far and near distances, but a review of literature suggests that ZFR00V has an advantage over existing multifocal and trifocal IOLs with regard to intermediate visual acuity (up to ∼2 line difference at 60 cm) and near visual acuity (eg, 0.8-line difference over TFNT00 IOL under photopic and mesopic conditions at 33 cm). 3,4,[6][7][8][9][10][11][12] In this study, ZFR00V improved binocular intermediate vision (UIVA) and near vision (UNVA and photopic and mesopic DCNVA), whereas the maintenance of far vision (CDVA) was similar to that observed with a monofocal ZCB00 IOL. Binocular DCNVA results under mesopic conditions in this study with ZFR00V (0.24) were similar to or better than DCNVA results from a previously published comparative analysis of TECNIS Symfony (0.30), PanOptix IQ (0.25), and AT LISA tri 839MP (0.27).…”
Section: Discussionsupporting
confidence: 64%
“…Secondary to the astigmatism assessment, Eom et al reported a binocular defocus curve for their patients [ 28 ]. Alió et al also evaluated the defocus curve of ten (Precizon 570 NVA) patients [ 29 ]. Despite differences in the intermediate VA level between the two studies, which may result from the small (10) study population analyzed by Alió's group, there are apparent similarities to the simulated VA in our study.…”
Section: Discussionmentioning
confidence: 99%